Influence Live Shopping And Affiliate Marketing On Impluse Buying On Tiktok Shop Application - Muhammad Burhanudin; Misbak Misbak; Jefri Romdony (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the effect of Live Shopping and Affiliate Marketing on Impulse Buying behavior among active Tiktok users. Using a quantitative approach with Partial Least Squares–Structural Equation Modeling (PLS-SEM), data were collected from 150 respondents dominated by young consumers aged 17–24 years, consisting mainly of students and university learners. The results of the direct effect hypothesis testing show that: (1) Live Shopping has a positive and significant effect on Impulse Buying with an original sample value of 0.376, supported by a t-statistic of 4,696 (>1.96) and a p-value of 0.000 (<0.05), indicating that H1 is accepted; (2) Affiliate Marketing has a strong positive and significant effect on Impulse Buying with an original sample value of 0.718, supported by a t-statistic of 8.911 (>1.96) and a p-value of 0.000 (<0.05), confirming that H2 is accepted; and (3) Live Shopping and Affiliate Marketing simultaneously have a significant effect on Impulse Buying, supported by a combined t-statistic of 7.319 (>1.96) and a p-value of 0.000 (<0.05), indicating that H3 is accepted. The findings confirm that interactive live promotional features and creator-based recommendation strategies effectively stimulate impulsive purchase decisions among young digital consumers. This study provides theoretical and practical contributions by emphasizing the importance of real-time engagement and social-persuasive marketing synergy in shaping impulse buying responses on e-commerce platforms